2015
DOI: 10.1016/j.icarus.2015.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Comets C/2007 D1 (LINEAR), C/2007 D3 (LINEAR), C/2010 G3 (WISE), C/2010 S1 (LINEAR), and C/2012 K6 (McNaught) at large heliocentric distances

Abstract: Photometric and spectroscopic observations of five nearly parabolic comets with eccentricity larger than 0.99 at heliocentric distances greater than 4 AU were performed. No molecular emission was observed for any studied comet and the entire cometary activity in all cases was attributed to dust production. Upper limits of the gas production rates for the main neutral molecules in the cometary comae were calculated. The derived values of dust apparent magnitudes were used to estimate the upper limit of the geom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…We observed this comet on the outward orbit between 5.70 AU (2008-03-31) and 7.24 AU (2009-04-19). Ivanova et al (2015) observed this comet about two weeks prior our fist observation, they derived derived an Afrho about 180-200 cm, which is consistent to our data.…”
Section: C/2007 D3 (Linear)supporting
confidence: 91%
See 1 more Smart Citation
“…We observed this comet on the outward orbit between 5.70 AU (2008-03-31) and 7.24 AU (2009-04-19). Ivanova et al (2015) observed this comet about two weeks prior our fist observation, they derived derived an Afrho about 180-200 cm, which is consistent to our data.…”
Section: C/2007 D3 (Linear)supporting
confidence: 91%
“…?s orbit at 5.2 AU (Meech & Svoren 2004). The main mechanisms that have been proposed to explain cometary activity of comets at large heliocentric distances are: the transition phase between amorphous and crystalline water ice (Prialnik 1992, Capria et al 2002, the annealing of amorphous water ice (Meech et al 2009), and the sublimation of more volatile admixtures like CO and/or CO2. In the past two decades, observational campaigns have been made to reveal the distant activity of comets, most by with observations of the Jupiter family (Meech 1991, O'Ceallaigh et al 1995Meech & Hainaut 1997;Lowry et al 1999;Szabó et al 2001;Szabó et al 2002;Korsun & Chörny 2003;Tozzi et al 2003;Szabó et al 2008;Mazzotta Epifani et al 2009;Meech et al 2009;Mazzotta Epifani et al 2010;Korsun et al 2010;Szabó et al 2012;Mazzotta Epifani et al 2014;Shi et al 2014;Ivanova et al 2015). However, there is still a lack in the observations of LP comets beyond 5.2 AU.…”
mentioning
confidence: 99%
“…Also, it was considered that the nature of the dust particles presented in cometary coma does not depend on the heliocentric distance (Dollfus et al 1988). However, new investigations show differences between the activity of comets close to the Sun and distant comets (see, e.g., Mazzotta Epifani et al 2007Ivanova et al 2011Ivanova et al , 2015bDlugach et al 2018). Most likely the particles which form the comae are different.…”
Section: Discussionmentioning
confidence: 99%
“…We refer the Reader to Ivanova et al (2015Ivanova et al ( , 2016 Siding Spring (Australia). Basic parameters of the telescopes are given in Table 1.…”
Section: Techniques Of Observation and Data Processingmentioning
confidence: 99%